1988
DOI: 10.1111/j.1745-4557.1988.tb00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Adjuncts for Restructured Pork

Abstract: Boneless prerigor pork shoulders were processed to restructured pork chops and formulated with I % NaCl and .25% sodium tripolyphosphate (STP). Formulations included (1) 100% pork (C) , (2) 95 % pork -5 % rehydrated dried apples (A), (3) 95 % pork -5 % mushroom slurry (M), and (4) 99.98 96 pork -.02 % liquid smoke extract (S). All samples were stored at -20 "C until evaluation at 0, 14 and 42 days afier packaging. Although the C chops received higher initial color scores, color of the A samples remained more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Studies conducted in our laboratories suggest that certain adjuncts function as flavor enhancers in restructured chops manufactured from postrigor pork (Marriott et al 1986) and prerigor pork (Marriott et al 1987).…”
Section: Introductionmentioning
confidence: 98%
“…Studies conducted in our laboratories suggest that certain adjuncts function as flavor enhancers in restructured chops manufactured from postrigor pork (Marriott et al 1986) and prerigor pork (Marriott et al 1987).…”
Section: Introductionmentioning
confidence: 98%
“…Other ingredients such as soy protein, oat fiber, collagen, konjac flour, and others have also been used in ground meat products (Arganosa et al 1987;McMindes 1991 ;Huffman et al 1992;Osburn and Keeton 1994). Marriott et al (1986;1988) studied incorporation of different flavor adjuncts to enhance the flavor of restructured pork. Inclusion of rehydrated apples yielded a product with improved flavor over that of pork without flavor enhancers (Marriott et al 1988).…”
mentioning
confidence: 99%
“…Marriott et al (1986;1988) studied incorporation of different flavor adjuncts to enhance the flavor of restructured pork. Inclusion of rehydrated apples yielded a product with improved flavor over that of pork without flavor enhancers (Marriott et al 1988). This suggested that incorporation of apple products into pork sausage formulations may improve the flavor of lower-fat formulations.…”
mentioning
confidence: 99%